Challenges of parents of young adults misusing psychoactive substances in small-scale mining communities in Ghana - Philip Asamoah; Samuel Nana Abokyi; Victor Fannam Nunfam (Cogent Mental Health)
Psychoactive substance misuse tends to affect the social, economic, and mental health of young adult users and their parents. However, there is currently limited research on the challenges of parents of young adults who misuse psychoactive substances. The stress-strain-coping-support theoretical model was used to assess the challenges parents of young adults who misuse psychoactive substances encounter in Ghana. Based on interpretive phenomenology, we purposively sampled and conducted in-depth interviews with 15 parents from the Adum-Banso Health Centre. Data was processed with NVivo 12 pro data and analysed thematically with four stages of Interpretative Phenomenological Analysis (IPA). The challenges of parents of young adults engaged in psychoactive substance misuse included financial constraints, the onset of negative emotional effects on parents, structural challenges in pursuit of medical treatment, and stigma and discrimination. We have provided empirical data to inform policy decisions on establishing social protection and psychosocial support schemes for young adults misusing psychoactive substances and their parents to enhance the rehabilitation of young adults recovering from the impacts of psychoactive substance misuse.